Characterization of a Monoclonal Antibody Specific to the Amino Terminus of the α-Chain of Human Fibrin - Mao, Simon J T; Rechtin, Ann E; Krstenansky, John L; Jackson, Richard L (Thrombosis and Haemostasis, 1990)
A peptide, Gly-Pro-Arg-Val-Val-Glu, corresponding to the first six residues of the amino terminus of the a-chain of human fibrin (desAA-fihrin) was prepared by solid-phase peptide synthesis. The peptide was covalently linked to keyhole-limpet hemocyanin (KLH) and used as an immunogen for preparing monoclonal antibodies. A monoclonal antibody specific to the hexapeptide, but not to KLH or fibrinogen, was produced. The antibody did not bind to thrombin-mediated clots prepared from either plasma or purified fibrinogen. However, immunoreactivity was detected when fibrin (prepared from fibrinogen) was solubilized with 8 M urea. In contrast, a monoclonal antibody specific to the amino terminus (Gly-His-Arg-Pro-Leu-Asp-Lys) of the (β-chain of fibrin recognized the epitope in clots. These results indicate that thrombin cleavage of fibrinogen produces a structural change in the amino terminal domain of the α-chain that makes it inaccessible to antibody interaction. In addition, our study suggests that the potential clinical application of monoclonal antibodies to localize fibrin-rich thrombi must take into account the final structure of clots.